IRRI's Digital and Data Strategy (Framework) - Gimena, Joy Marie (International Rice Research Institute, 2026)
Our global environmental, nutritional, and AI landscapes are changing. As a non-partisan international organization, we have a unique position to partner with regional and global organizations to drive climate resilience, address health challenges, and integrate solutions for improved livelihoods. Partners and country governments are already adapting by investing in climate resilient and nutritionally sustainable breeding pipelines, digital public infrastructure, and data driven support tools (for themselves and farmers). The private sector requires real-world data and expertise to validate models, fine tune se rvice offerings, and integrated solutions for bundling to ensure sustainable business models. A fragmented agricultural food system with complex needs and increasingly more private sector players requires connected and data-informed digital solutions to drive transformation across the food system's value chain. IRRI and CGIAR must establish strong partnerships in the ASEAN region to support South-South collaboration, and integrated data-driven, accessible solutions.